Glucosylated caffeoylquinic acid derivatives from the flower buds of Lonicera japonica - Yu, Yang (Acta Pharm Sin B, 2015)
Three new glucosylated caffeoylquinic acid isomers (1–3), along with six known compounds, have been isolated from an aqueous extract of the flower buds of Lonicera japonica. Structures of the new compounds were determined by spectroscopic and chemical methods as (−)-4-O-(4-O-β-d-glucopyranosylcaffeoyl)quinic acid (1), (−)-3-O-(4-O-β-d-glucopyranosylcaffeoyl)quinic acid (2), and (−)-5-O-(4-O-β-d-glucopyranosylcaffeoyl)quinic acid (3), respectively. In the preliminary in vitro assays, two known compounds methyl caffeate and 2ʹ-O-methyladenosine showed inhibitory activity against Coxsackie virus B3 with IC(50) values of 3.70 μmol/L and 6.41 μmol/L and SI values of 7.8 and 12.1, respectively.